Endolichenic fungal diversity associated with some lichens of the Western Ghats - Rajulu, Meenavalli Babu Govinda; Thirunavukkarasu, Nagamani; Kumar, Subramanya Shravan; Kaur, Tanveer; Reddy, Mondem Sudhakara; Suryanarayanan, Trichur Subramanian (Planta Medica, 2019)
A total of 389 strains of fungi belonging to 38 species were isolated from 10 lichen species of the Western Ghats, southern India. All the lichens screened, irrespective of their growth forms or location, harboured endolichenic fungi. Most of the fungi belonged to the Ascomycotina. Chaetomium sp. 1, Hypoxylon investiens, Nemania bipapillata, Nodulisporium sp., Paecilomyces sp., and Sporormiella intermedia were the most common ones and were present in 5 or more lichen species. Of the 28 sporulating fungi, 7 belonged to Xylariales, and their total colonization frequency in all the lichens was also high. This observation further substantiates the high ecological amplitude of Xylariales, possibly due to overlapping ecological niches and their ability to inhibit co-occurring endolichenic fungi.
Keywords: endophytic fungi; host jump; host range; microbiome; Xylaria